'Omics driven discoveries of gene targets for apoptosis attenuation in CHO cells. Issue 1 (9th September 2020) - Orellana, Camila A.; Martínez, Verónica S.; MacDonald, Michael A.; Henry, Matthew N.; Gillard, Marianne; Gray, Peter P.; Nielsen, Lars K.; Mahler, Stephen; Marcellin, Esteban
Abstract: Chinese hamster ovary (CHO) cells are widely used in biopharmaceutical production. Improvements to cell lines and bioprocesses are constantly being explored. One of the major limitations of CHO cell culture is that the cells undergo apoptosis, leading to rapid cell death, which impedes reaching high recombinant protein titres. While several genetic engineering strategies have been successfully employed to reduce apoptosis, there is still room to further enhance CHO cell lines performance. 'Omics analysis is a powerful tool to better understand different phenotypes and for the identification of gene targets for engineering. Here, we present a comprehensive review of previous CHO 'omics studies that revealed changes in the expression of apoptosis‐related genes. We highlight targets for genetic engineering that have reduced, or have the potential to reduce, apoptosis or to increase cell proliferation in CHO cells, with the final aim of increasing productivity. Abstract : This review highlights targets for genetic engineering that have the potential to reduce apoptosis or to increase cell proliferation in CHO cells. By revising previous CHO 'omics studies, various apoptosis‐associated genes were found to be de‐regulated in phenotypes of interest, such as increased productivity. The overexpression or downregulation of these targets have successfully reduced apoptosis or increased cell proliferation in various cancer cells, and are consequently promising targets for CHO cell engineering.